1996
DOI: 10.1074/jbc.271.44.27575
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the Nicotinic Acetylcholine Receptor

Abstract: To investigate the mechanism of assembly of the mouse muscle acetylcholine receptor, we have expressed truncated N-terminal fragments of the ␣ and ␦ subunits in COS cells and have examined their ability to fold, to associate into heterodimers, and to form a ligand-binding site. Truncated fragments of the ␣ subunit that include all, part, or none of the first transmembrane domain (M1) folded to acquire ␣-bungarotoxin binding activity. Neither the full-length ␣ subunit nor any of the fragments were expressed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 49 publications
(84 reference statements)
1
31
0
Order By: Relevance
“…Additional chimeric proteins and fragments should in future experiments allow a more detailed analysis of this assembly domain. The key role of N-terminal domains for subunit assembly found here mirrors a similar importance of these regions for assembly of other ion channels, for example nicotinic acetylcholine, GABA A , and glycine receptors, as well as potassium channels (26,56,59,60,64,65). The advantages of such an arrangement are presently unclear.…”
Section: Constructmentioning
confidence: 53%
See 2 more Smart Citations
“…Additional chimeric proteins and fragments should in future experiments allow a more detailed analysis of this assembly domain. The key role of N-terminal domains for subunit assembly found here mirrors a similar importance of these regions for assembly of other ion channels, for example nicotinic acetylcholine, GABA A , and glycine receptors, as well as potassium channels (26,56,59,60,64,65). The advantages of such an arrangement are presently unclear.…”
Section: Constructmentioning
confidence: 53%
“…They indicate that this half of the protein does not play an important role in subunit assembly. Deletion of the first transmembrane region strongly reduced association, as has been shown for the assembly of nicotinic acetylcholine receptors and potassium channels (26,59,60). The association of two fusion proteins in which the first transmembrane domain was replaced by the third showed that the sequence of this domain was not important for assembly.…”
Section: Constructmentioning
confidence: 79%
See 1 more Smart Citation
“…M1, however, played an important role for expressing these extracellular domain nAChRs. These results, with the properties of extracellular domain ␣7 nAChRs (33,34) and evidence of oligomerization of extracellular domains from ␣1 and ␦ subunits (31,32), from extracellular domains of muscle-type subunits (35), from chimeric ␣7/AChBP subunits (26), from glycine receptor subunits (68,69), and from GABA A receptor subunits (70), suggest that producing extracellular domain receptors might be possible for many subunits throughout the nicotinoid family. Expression of extracellular domain nicotinoid receptors with high structural fidelity, however, might be more feasible with M1 included in the subunit design than without M1.…”
Section: Discussionmentioning
confidence: 76%
“…They have been expressed with several subunit combinations. Dimeric extracellular domain nAChRs were produced by extracellular domains of ␣1 and ␦ subunits that also contained M1 or another membrane tether, suggesting that membrane attachment of subunits might be important for forming these extracellular domain nAChRs (31,32). Extracellular domains of ␣7 subunits linked to a glycosylphosphatidylinositol moiety were transported to the surface of Xenopus oocytes and bound ␣-bungarotoxin (␣Bgt) and d-tubocurarine (33), implying the formation of multimers.…”
Section: Nicotinic Acetylcholine Receptors (Nachrs)mentioning
confidence: 99%